2016
DOI: 10.1016/j.rboe.2016.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Keblish's lateral surgical approach enhances patellar tilt in valgus knee arthroplasty

Abstract: ObjectiveTo compare the clinical and radiological outcomes of conventional medial and lateral approaches for total knee replacement in the valgus osteoarthritic knee.MethodsIn this randomized controlled trial, 21 patients with valgus knee osteoarthritis were randomized to total knee replacement through medial or lateral approach. The primary outcome was radiographic patellar tilt. Secondary outcomes were visual analog scale of pain, postoperative levels of hemoglobin, and clinical aspect of the operative wound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…When comparing the results of the surgeries performed with and without a tourniquet, no clear benefit was observed for either, as the greater amount of pain exhibited by the non-tourniquet group was only evident for a short period, and the improved mobility in the latter was not observed at a clinically relevant level. The lateral via provided better postoperative lateral patellar tilt in valgus knee arthroplasties 55 . The ERAS Program is safer and more effective in elderly patients with TKA compared to the traditional route.…”
Section: Discussionmentioning
confidence: 93%
“…When comparing the results of the surgeries performed with and without a tourniquet, no clear benefit was observed for either, as the greater amount of pain exhibited by the non-tourniquet group was only evident for a short period, and the improved mobility in the latter was not observed at a clinically relevant level. The lateral via provided better postoperative lateral patellar tilt in valgus knee arthroplasties 55 . The ERAS Program is safer and more effective in elderly patients with TKA compared to the traditional route.…”
Section: Discussionmentioning
confidence: 93%
“…Filho et al. 21 found that a lateral approach provided better patellar tilt following TKA in valgus osteoarthritic knees. Finally, Niki et al.…”
Section: Discussionmentioning
confidence: 99%
“…Chalidis et al 31 found that a lateral approach combined with TTO was an effective technique for addressing non-correctable valgus deformity during TKA. Filho et al 21 found that a lateral approach provided better patellar tilt following TKA in valgus osteoarthritic knees. Finally, Niki et al 19 found that lateral minimally invasive TKA might offer a useful technical option that can be utilized for most patients with valgus deformity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is recognized that the correction of a valgus deformity has technical particularities that need to be recognized by the knee surgeon when performing a TKA. It comprises surgical approach, bone cuts, and mostly ligament balance [1,2,4].…”
Section: Introductionmentioning
confidence: 99%